The impact of textual input enhancement on Iranian elementary EFL learners' vocabulary intake - Nahavandi, Naemeh; Mukundan, Jayakaran (Canadian Center of Science and Education, 2014)
Nowadays, there has been a lot of emphasis on L2 vocabulary learning in the language teaching curriculum. Dueto the emergence and prevalence of growing methods in the area of second language teaching, lots of researchershave tried to take advantage of these methods in enhancing L2 learning vocabulary. Thus, the present studyinvestigated the effect of textual input enhancement as a focus on form method on Iranian EFL learners’vocabulary intake from reading. Ninety one elementary EFL learners in Tabriz Azad University participated in astudy for eight sessions. A quasi-experimental design with a randomized control and an experimental group wasused. Both groups were given five reading texts and comprehension questions to complete. While theparticipants in experimental group read the textually enhanced input through bolding, the participants in thecontrol group read the same texts without input manipulation. Multiple-choice recognition tests were used tomeasure the intake of vocabulary. The results showed a significant difference between control and experimentalgroup. The study concluded with some pedagogical implications.